2015
DOI: 10.1002/alr.21540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of allergic rhinitis on quality of life among Thai students

Abstract: The prevalence of AR at a college campus was 58.5%. The presence of rhinitis symptoms was the highest predictor of the presence of AR, with 67.7% having subsequent positive SPT. Students with AR had poorer scores in every dimension of QoL as defined by the Rcq-36 when compared to their non-AR counterparts. Educational performances among the 2 groups were unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…medical students in Thailand did not find allergic rhinitis to impact on academic performance, despite it adversely affecting quality of life. 7 Sleep disturbance was not a prominent complaint, in contrast with the findings of other studies.…”
Section: Past and Current Treatmentcontrasting
confidence: 78%
See 1 more Smart Citation
“…medical students in Thailand did not find allergic rhinitis to impact on academic performance, despite it adversely affecting quality of life. 7 Sleep disturbance was not a prominent complaint, in contrast with the findings of other studies.…”
Section: Past and Current Treatmentcontrasting
confidence: 78%
“…6 The prevalence of allergic rhinitis in the university population of Bangkok was reported to be between 57.4% and 61.9%, as compared with the prevalence in the general population of 44.2%. 7 Although most participants felt that their rhinitis was allergic in nature, a minority had had their allergy confirmed by allergy tests. The most commonly reported allergens were pollen, dust, cats and grass.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies have shown that the prevalence of AR varies between 10% and 58.5% according to geographical regions. [5][6][7] The rate of AR in adults has been reported at around 21% in Europe, 25% in Canada, 27% in South Korea, and 32% in the United Arab Emirates. [8][9][10][11] A 2015 study conducted with university students revealed a 58.5% AR prevalence and the students with AR reported a lower quality of life.…”
Section: Background/rationalementioning
confidence: 99%
“…[8][9][10][11] A 2015 study conducted with university students revealed a 58.5% AR prevalence and the students with AR reported a lower quality of life. 7 It is stated that the most common allergic disease in Turkey is AR. 12 The rate of allergies in Turkey is shown in different studies in the range of 7-25%.…”
Section: Background/rationalementioning
confidence: 99%
See 1 more Smart Citation